2006
DOI: 10.1002/cncr.22004
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicity from high‐dose use of platinum compounds in patients with neuroblastoma

Abstract: BACKGROUND. The young age of neuroblastoma patients makes them especially prone to the ototoxic effects of widely used treatments that feature aggressive use of platinum compounds. We present data defining the extent of the problem in a large series of neuroblastoma patients whose induction included high-dose cisplatin/etoposide (HD-P/E) as used in both the Memorial Sloan-Kettering Cancer Center N7 regimen and the Children's Oncology Group A3973 study.METHODS. N7/A3973 patients were divided into 3 groups: Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
105
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 33 publications
7
105
2
2
Order By: Relevance
“…[5][6][7] Such survivorship research in the pediatric setting has focused primarily on the more common malignancies, such as acute lymphoblastic leukemia and Hodgkin's lymphoma, with very little systematic study on late effects of neuroblastoma, perhaps with the exception of documenting the permanent ototoxic effects of cisplatin and carboplatin. [8][9][10][11][12] From the present study 4 and similar clinical followup work by Laverdie`re et al 13 and others, 14 we can reach a brief understanding of the risks for multi-organ sequelae among survivors of advanced stage neuroblastoma. The most prominent are endocrine impairments, including short stature, hypothyroidism and ovarian and testicular dysfunction; musculoskeletal complications, including kyphosis and scoliosis, significant dental abnormalities, slipped capital femoral epiphysis, fractures, fibrosis and hypoplasia; major organ system impairment, most notably serious renal dysfunction, but also cardiac toxicity and lung fibrosis or other pulmonary problems; neurological disorders, including opsoclonus myoclonus (opsoclonus ataxia), neurogenic bladder, and paresis and paraplegia; and sensory impairments, including chronic pain, parasthesia, cataracts and neurosensory hearing loss.…”
supporting
confidence: 74%
“…[5][6][7] Such survivorship research in the pediatric setting has focused primarily on the more common malignancies, such as acute lymphoblastic leukemia and Hodgkin's lymphoma, with very little systematic study on late effects of neuroblastoma, perhaps with the exception of documenting the permanent ototoxic effects of cisplatin and carboplatin. [8][9][10][11][12] From the present study 4 and similar clinical followup work by Laverdie`re et al 13 and others, 14 we can reach a brief understanding of the risks for multi-organ sequelae among survivors of advanced stage neuroblastoma. The most prominent are endocrine impairments, including short stature, hypothyroidism and ovarian and testicular dysfunction; musculoskeletal complications, including kyphosis and scoliosis, significant dental abnormalities, slipped capital femoral epiphysis, fractures, fibrosis and hypoplasia; major organ system impairment, most notably serious renal dysfunction, but also cardiac toxicity and lung fibrosis or other pulmonary problems; neurological disorders, including opsoclonus myoclonus (opsoclonus ataxia), neurogenic bladder, and paresis and paraplegia; and sensory impairments, including chronic pain, parasthesia, cataracts and neurosensory hearing loss.…”
supporting
confidence: 74%
“…Previous studies have revealed hearing impairments mainly in patients <5 years old (20,24,25). In the adult group, hearing impairments were identified in 6/17 (35.3%) patients.…”
Section: Discussionmentioning
confidence: 90%
“…Audiologically, there are monitoring proposals using conventional frequencies (Testa et al 15 , Kushner et al 16 , Marshall et al 17 , Toral-Martinnon et al 18 ), monitoring proposals using transient otoacoustic emissions (Liberman 19 ) or distortion products (Biro et al 20 ; Hyppolito et al 21 ), and monitoring proposals using high frequencies (over 8000 Hz) (Garcia 22 ), which may be first affects by ototoxic drugs. In this case, patients with hearing loss normally do not complain and not always perceive loss of hearing (Liberman 23 ).…”
Section: Discussionmentioning
confidence: 99%